European Integration Influence on the Development of Human Capital of Small and Medium Enterprises in Poland - Marzena Kacprzak; Agnieszka Król; Marta Radziszewska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Enterprises from the SME sector significantly affect the quality of human capital in Poland and the standards of their management are rising every year. The aim of this article is to present the essence and specifics of human capital of SMEs, showing the impact of European integration on the devel-opment of human capital in this sector. In addition, the authors focus on finding the answer to the question whether employers willingly reach for EU funding (sources of knowledge, forms, types of funding, barriers to access to funds) to be able to support and develop human capital that they have in the long run. The study was carried out by a survey method. The analysis made allowed to formu-late the following conclusions. Entrepreneurs willingly undertake to raise funds from EU funds. Re-spondents were convinced that EU funds help in the development of their businesses, although ob-taining funding alone is not easy. The respondents pointed to barriers, which include complicated and lengthy procedures, as well as low availability of information.